Transition of care from post-acute services for the older adults in Quebec: a pilot impact evaluation - Shashank Ghai; Kathleen Chassé; Marie-Jeanne Renaud; Lilian Guicherd-Callin; André Bussières; Diana Zidarov (BMC, 2024)
Abstract Background Early discharge of frail older adults from post-acute care service may result in individuals' reduced functional ability to carry out activities of daily living, and social, emotional, and psychological distress. To address these shortcomings, the Montreal West Island Integrated University Health and Social Services Centre in Quebec, Canada piloted a post-acute home physiotherapy program (PAHP) to facilitate the transition of older adults from the hospital to their home. This study aimed to evaluate: (1) the implementation fidelity of the PAHP program; (2) its impact on the functional independence, physical and mental health outcomes and quality of life of older adults who underwent this program (3) its potential adverse events, and (4) to identify the physical, psychological, and mental health care needs of older adults following their discharge at home. Methods A quasi-experimental uncontrolled design with repeated measures was conducted between April 1st, 2021 and December 31st, 2021. Implementation fidelity was assessed using three process indicators: delay between referral to and receipt of the PAHP program, frequency of PAHP interventions per week and program duration in weeks. A battery of functional outcome measures, including the Functional Independence Measure (FIM) and the Patient-Reported Outcomes Measurement Information System (PROMIS) Global-10 scale, as well as fall incidence, emergency visits, and hospitalizations were used to assess program impact and adverse events. The Patient's Global Impression of Change (PGICS) was used to determine changes in participants' perceptions of their level of improvement/deterioration. In addition, the Camberwell Assessment of Need for the Elderly (CANE) questionnaire was administered to determine the met and unmet needs of older adults. Results Twenty-four individuals (aged 60.8 to 94 years) participated in the PAHP program. Implementation fidelity was low in regards with delay between referral and receipt of the program, intensity of interventions, and total program duration. Repeated measures ANOVA revealed significant improvement in FIM scores between admission and discharge from the PAHP program and between admission and the 3-month follow-up. Participants also reported meaningful improvements in PGICS scores. However, no significant differences were observed on the physical or mental health T-scores of the PROMIS Global-10 scale, in adverse events related to the PAHP program, or in the overall unmet needs. Conclusion Findings from an initial sample undergoing a PAHP program suggest that despite a low implementation fidelity of the program, functional independence outcomes and patients' global impression of change have improved. Results will help develop a stakeholder-driven action plan to improve this program. A future study with a larger sample size is currently being planned to evaluate the overall impact of this program. Clinical trial registration Retrospectively registered NCT05915156 (22/06/2023).